The uncertainties in the estimation of electricity production in the Brazilian onshore wind sector - Jéssica Cunha Pinheiro; Raphael Amaral da Câmara (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
Wind energy has emerged as a key component of the global transition to renewable sources. In Brazil, the onshore wind sector has experienced significant growth, accounting for approximately 16% of the country’s electricity generation. However, estimating wind energy production is subject to various uncertainties that can impact project feasibility, financial viability, and energy security. This study analyzes the key uncertainties in electricity production estimation, focusing on four pillars: accuracy, correlation, consistency, and corroboration. Accuracy concerns wind measurement precision, affected by instrument calibration, sensor placement, and data collection. Correlation involves long-term data adjustments, ensuring reliable resource assessment. Consistency addresses the integration of environmental factors into wind turbine performance models, while corroboration verifies data reliability through power curve validation. These uncertainties directly influence the expected energy output, affecting investment decisions and regulatory compliance. To mitigate risks, this study discusses best practices such as adopting high-precision measurement techniques, improving data processing models, and following regulatory guidelines set by the Energy Research Company (EPE), a Brazilian organization. The findings highlight the need for continuous advancements in forecasting methodologies to enhance reliability and investor confidence. By addressing these uncertainties, the Brazilian wind sector can achieve greater predictability in energy production, strengthening its role in a sustainable and diversified energy matrix.